Roman victory propaganda – Revelation’s response: A historical and theological study - Łukasz Bergel (HTS Teologiese Studies/Theological Studies)
The believers of Christ in the 1st century AD find themselves in a difficult situation. On one hand, they receive the gospel about Jesus’ victory over the world. On the other hand, they witnessed the power and dominance of the Roman Empire through its propaganda. The Book of Revelation comes with a message to comfort Christians torn between these two realities. It uses the Roman symbolism of victory and transforms it to answer the Roman propaganda. Thus, Revelation creates a powerful and vivid message to convince the reader that God is the supreme and only ruler of the world, and Christ triumphs over every power, even the invincible Roman Empire.